A análise de Kelsen e Bobbio das distinções kantiana entre direito e moral - Pedroso, Greici Inticher (2007)
The present thesis presents the main Kantian notions for the distinction between law and moral, exemplified, first through, the hypothetic imperatives and categorical imperatives. The existence of others methods to make the distinction in focus makes necessary the stipulation of other views capable to accomplish the task is, as the concepts of internal and external legislation, autonomy and heteronomy, duties, and others. From such distinctions our objective is to make an analysis and survey of the reception of the law philosophers Hans Kelsen and Norberto Bobbio, well-known ones in the contemporary legal field, for their own conceptions, and for the criticisms of the positioning of Kant, showing a connection of those with Kant, even though, a positive influence of Kant. Is highlighted the fact that, in one hand, there is a legal naturalism conception, opposed, on the other hand, legal positivism conceptions. In this direction, the possible transposition of plans, the foundation and the application, is then inevitable, such as it weakens the vigor of such criticisms.